The effect of smoking on placental pendrin expression*. (2nd January 2017) - Karatas, Ahmet; Erdem, Havva; Karatas, Zehra; Ozlu, Tulay; Cakmak, Bulent
Abstract: Pendrin is important for transport of iodine across the placenta. Thiocyanate coming from cigarette is a competitive inhibitor of iodine transport. We aimed to evaluate the pendrin immunostaining intensity in placentas of smoker and non-smoker women. Placental tissues from 61 women, of which 28 were in smoking, and 33 were in non-smoking group were evaluated by immunohistochemical staining. Positive immunostaining was evaluated using a semiquantitative score: 0, negative; +, mild; ++, moderate; and +++, intense. Birth weight was significantly lower in the smoker group ( p = 0.024). There was a negative correlation between birth weight and intensity of placental pendrin immunostaining in the smoker group ( r = −0.44, p = 0.02). Placentas of the smoking women showed significantly higher immunostaining with pendrin than the control group ( p = 0.006). Thiocyonate coming from cigarettes may competitively inhibit pendrin mediated iodine transport in the placenta and adversely affect foetal development by this mechanism.